Analysis of Obstacles in the Learning Process in Class IV Inclusion School SDN Pojok - Arfina, Sifana Fahma; Setiawan, Angga Bayu; Handayani, Octavia Putri; Arfina, Anggi; Danuri, Danuri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to analyze the obstacles experienced in the learning process in the inclusion class at SD Negeri Pojok. The type of research used is qualitative research with the subjects being teachers and fourth grade students. Data collection was carried out by observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the research show that what can hinder learning in inclusive classes are: 1) lack of motivation to learn for students with special needs, 2) lack of concentration for students with special needs, 3) differences in intelligence, 4) lack of self-confidence for students with special needs, and 5) lack of confidence. teachers in dealing with students with special needs. Factors that influence these obstacles are parental factors and teacher competency factors.